What does border externalization mean and what impact do the migration policies of the EU have on migrants' and refugees' human rights? What are the legal consequences for states that commit the human rights violations? - Winter, Isabella (Department of Public Law, 2022)
The EU is well-known for its policy of externalisation, that is, shifting the migration control away from its own borders (as a second, destination country) and towards third countries. This practice challenges human rights law. The thesis addresses the meaning and development of the border externalization. Furthermore, it explains how the migration policies are impacting migrants' and refugees' human rights. Finally, the thesis argues that states can be held responsible for the human rights violations happening due to the EU's policy of externalisation. Thus, overall, the thesis is concerned with the EU migration control and its member states and the human rights situation in Libya. The migration policies have changed in the past to new forms of non-entrée in which the border control is carried out by the authorities of the state of origin or transit. This is, because the early non-entrée practices were legally challenged, and did not protect European states from legal accountability. By funding the Libyan Coast Guards and entering agreements with a politically unstable country that also has a poor human right record, the EU and its member states are supporting the violations of migrants' and refugees' rights. These violations range from breaches of the right to life, the right to seek and enjoy asylum, the principle of non-refoulment, the right against torture and ill-treatment, the right to liberty, and the right to remedy. The violations are especially grave in migration-related detention in Libya where detainees experience inhuman living conditions and abuse. The thesis argues that the EU and its member states, particularly Italy due to the special cooperation between the Italian and Libyan authorities, are in breach of international as well as European law. The thesis concludes that state responsibility follows from Article 16, 17, and 47 ARSIWA are violated as well as Article 3 ECHR.